Nesrea And Ncc Regulations On Telecommunication Masts: Implementing The Precautionary Principle - Ogboru, Tolulope (Journal of Sustainable Development Law and Policy, 2025)
There have been conflicting findings in studies conducted to determine whether or not electromagnetic radiations (EMR) emitted by telecommunication masts are injurious to human health and the environment. The recent imbroglio between the National Environmental Standards and Regulations Enforcement Agency (NESREA) and the Nigerian Communications Commission (NCC) brought this matter to the fore in Nigeria. The conflict relates to the set back distance telecommunication operators are required to adopt as they site their masts near buildings. While NESREA’s Regulation provides for a farther distance because of its belief that electromagnetic radiations do have adverse impact on human health; NCC on the other hand insists that EMR does not pose any danger to human health. Having examined literature, report of studies and various opinions, it is evident that the scientific community is yet to agree on the effects of EMR on human health and the environment. This paper argues that this lack of scientific certainty should not be a reason to delay legislative action that will safeguard people’s health and their environment. The paper evokes the importance of the precautionary principle of international law to the effect that lack of full scientific evidence should not be used as a reason for postponing measures to prevent irreversible illnesses and environmental degradation that may result from EMR emitted by telecommunication masts. This paper discusses the need for regulatory agencies and the legislature to adopt the precautionary principle as they review and harmonise the two overlapping Regulations.